2016
DOI: 10.1097/ogx.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computed Tomography for Gynecologic Malignancies

Abstract: PET/CT plays an important role in detection of initial disease and recurrence of gynecologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…18 F-FDG PET/CT is useful for the assessment ovarian cancer recurrence [18]. It is able to find lesions in many instances in which CT alone is negative, and it is able to detect disease recurrence 6 months before findings can be seen on CT [19].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is useful for the assessment ovarian cancer recurrence [18]. It is able to find lesions in many instances in which CT alone is negative, and it is able to detect disease recurrence 6 months before findings can be seen on CT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Given that these techniques can be used to visualize vascularization and glucose transport, which are characteristics of malignant cells, they are useful (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early diagnosis and treatment of an ovarian tumor is very important. For the differentiation of ovarian masses and the decision to apply surgery, the diagnostic methods to be used include physical examination, biochemical markers (5), ultrasonography (US) (6,7), magnetic resonance imaging (MRI) (8), positron emission tomography (PET) (9) and computed tomography (CT) (8,9). In previous studies, it has been reported that MRI is superior to CT and US in the differential diagnosis of ovarian masses but that there was no difference between these methods in malignantbenign differentiation (10).…”
Section: Introductionmentioning
confidence: 99%